2021
DOI: 10.4166/kjg.2021.123
|View full text |Cite
|
Sign up to set email alerts
|

Colon Polyp Detection in Primary Health Care Institutions of Korea: Detection Rate and Issues with Following the Guidelines

Abstract: Background/Aims: There have been few multicenter studies on colonic polyps conducted by primary medical institutions. This study examined the detection rate of colonic polyps in primary health care institutions and the related factors while following the guidelines. Methods: The medical records of 14,029 patients who underwent colonoscopy between January-June 2020 at 40 primary medical institutions in Korea were analyzed. High-risk adenoma was defined as advanced adenoma, carcinoma, or ≥3 adenomas. Results: Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…By comparison, we found that only when CRN occurred in the proximal colon did the proportion of women exceed that of men, which is consistent with previous findings that women are at higher risk for CRC in the proximal colon [14], especially in the ascending colon [9]. In many studies, advanced age is a risk factor for colorectal adenoma and colorectal cancer [9,12,15,16]. This may be related to the adenoma-carcinoma sequence of colorectal tumors [5,17]; when normal cells accumulate multiple genetic mutations over many years, they become cancerous [18,19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By comparison, we found that only when CRN occurred in the proximal colon did the proportion of women exceed that of men, which is consistent with previous findings that women are at higher risk for CRC in the proximal colon [14], especially in the ascending colon [9]. In many studies, advanced age is a risk factor for colorectal adenoma and colorectal cancer [9,12,15,16]. This may be related to the adenoma-carcinoma sequence of colorectal tumors [5,17]; when normal cells accumulate multiple genetic mutations over many years, they become cancerous [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…Age over 70 years was most associated with the risk of CRN in the proximal colon among women and rectal CRN among men. Men are more likely to develop CRN than women, possibly because men lack the protective effect of estrogen [12]. Moreover, it has been suggested that androgens may be involved in the formation of colorectal tumors by regulating the proliferation of intestinal epithelial cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from primary health-care institutions in Korea, the proportion of incomplete examinations attributed to poor bowel preparation or difficulty in cecal intubation was only 4.9%. 49 In addition, most hospital-based studies on screening colonoscopy in Korea reported a high CIR of nearly 100%. 50 As the primary health-care institutions are sufficiently achieving the target CIR (≥95%), the CIR may have little room for improvement in Korea.…”
Section: Cecal Intubation Ratementioning
confidence: 99%
“…Анализирана е документацията на 14029 болни -6949 мъже на средна възраст от 55,9±13,4 г. и 7080 жени на средна възраст от 57,2±12,7 г., подложени на колоноскопия в 40 първични медицински институции в Южна Корея с цел диагностика на полипите на дебелото черво (13). Честотата на полипите на дебелото черво, аденомите, аденомите в напреднал стадий и аденомите с висок риск е съответно 59,9%, 38,9%, 5,9% и 11,4% от колоректални полипи (31,97%; между 30,97% и 33,28% при доверителен интервал от 95%) в сравнение с контролната група (25,9%; между 25,1% и 26,72% при доверителен интервал от 95%) при фактическо съотношение между стойностите на тази заболяемост от 1,235 (между 1,174 и 1,300 при доверителен интервал от 95%) (3).…”
Section: въведениеunclassified